Le carnet de voyage au xviie siècle : Du terme de négoce au calligramme - Sylvie Requemora (Viatica, 2018)
In the 17thcentury, travellers described what they saw during their travels, but they also took careful note of what they spent or earned. In this sense, the "journal" is more a statement of account than a literary object. After tracing Melchisédech Thévenot’s impressive collection of handwritten notebooks - a collection of curiosities, texts and foreign objects - and studying the use of the notebooks intended for publication by his nephew Jean Thévenot, the author focuses on the remarkable case of Accarette, who transformed his notebook into a calligram.